Novel Results of K Quasi (ℷ-M)-hyponormal Operator - Salim Dawood Mohsen (Iraqi Journal of Science, 2024)
This research aims to present some results for conceptions of quasi -hyponormal operator defined on Hilbert space . Signified by the -operator, together with some significant characteristics of this operator and various theorems pertaining to this operator are discussed, as well as, we discussed the null space and range of these kinds of operators.